Clinical Predictors of Emergency Department Revisits within 48 Hours of Discharge; a Case Control Study - Tangkulpanich, Panvilai; Yuksen, Chaiyaporn; Kongchok, Wanchalerm; Jenpanitpong, Chestsadakon (Archives of Academic Emergency Medicine, 2021)
Introduction: Emergency department (ED) revisits increase overcrowding and predicting which patients may need to revisit could increase patient safety. This study aimed to identify clinical variables that could be used to predict the probability of revisiting ED within 48 hours of discharge. Methods: A retrospective case-control study was conducted between July 2018 and January 2019 at the Emergency Medicine Department in Ramathibodi Hospital, Bangkok, Thailand. Patients who revisited the ED within 48 hours of discharge (case group) and patients who did not (control group) participated. The predictive factors for ED revisit were identified through multivariate logistic regression analysis. Results: The case group consisted of 372 patients, who revisited the ED within 48 hours, and the control group consisted of 1488 patients. The most common reason for revisiting the ED was recurring gastrointestinal illness, in 107 patients (28.76%). According to the multivariate data analysis , five factors influenced the probability of revisiting the ED: age of more than 60 years (p < 0.001, OR = 2.04, 95%CI: 1.51-2.77), initial Emergency Severity Index (ESI) triage level of 2 (p = 0.007, OR = 1.20, 95%CI: 0.93-1.56), ED stay duration of 4 hours or longer (p = 0.013, OR = 1.12, 95%CI: 0.87-1.44), body temperature of ≥37.5ºC on discharge (p = 0.034, OR = 1.34, 95%CI: 1.00-1.80), and pulse rate of less than 60 (OR = 1.55, 95%CI: 0.87-2.77) or more than 100 beats/minute (OR = 1.53, 95%CI: 1.10-2.11) (p = 0.011). Conclusion: According to the findings, the most important and independent predictive factor of ED revisit within 48 hours of discharge were, age ≥ 60 years, ESI triage level 2, ED length of stay ≥ 4 hours, temperature ≥ 37.5 C, and 60 > pulse rate ≥ 100 beats/minute.